Synthesis, aggregation-induced emission (AIE) and electroluminescence of carbazole-benzoyl substituted tetraphenylethylene derivatives. (February 2020) - Zhan, Yingying; Yang, Zhiwen; Tan, Jihua; Qiu, Zhipeng; Mao, Yuanyou; He, Jia; Yang, Qingdan; Ji, Shaomin; Cai, Ning; Huo, Yanping
Abstract: Aggregation-induced emission (AIE) materials offer a solution to obtain high fluorescence efficiencies in solid state which is desirable for optoelectronic devices and display. Here in this work, three new types of D-π-A-π-D AIE luminogens based on carbazole-benzoyl substituted tetraphenylethylene (TPE) derivatives were designed and successfully synthesized. Meanwhile, their photophysical properties as well as electroluminescence (EL) characteristics were studied. These luminogens show good AIE property with high solid-state fluorescence quantum yields. Furthermore, the emission wavelengths for these three luminogens, both in solutions and in solid state, exhibit negligible variation by increasing the number of donor group. All three luminogens show solvatochromism and negative solvatokinetic effect in different solvents. More interesting is that on increasing number of donor groups, their thermal and morphological stability present regular change by increasing the number of carbazole-benzoyl group. The performance of non-doped OLED device based on TPE-3BZ-Cz is superior than the other two luminogens, which has been proved by further electroluminescence evaluation. Graphical abstract: Image 1 Highlights: Three novel D-π-A-π-D type luminogens based on carbazole-benzoyl substituted tetraphenylethylene derivatives are developed. TPE-BZ-Cz, TPE-2BZ-Cz, and TPE-3BZ-Cz exhibit AIE characteristics and high solid-state luminescence efficiency. The relationship between the photophysical property and D-π-A-π-D structure are discussed.